Kinematics and Workspace Analysis and Numerical Simulation of the 3-PRRRR Parallel Manipulator - Shi Mengrui; Zhaoxinhua (Jixie chuandong)
The Working space is an important performance and design index in evaluating parallel manipulator.The 3-PRRRR parallel manipulator branched chain is simplified reasonably,by using the D-H method,the 3-PRRRR parallel manipulator inverse kinematic analysis is carried out,the equation of inverse kinematic analysis is obtained.By using the MATLAB,the numerical simulation of its inverse kinematic analysis is carried out.According to the characteristic of the 3-PRRRR parallel manipulator,by choosing the method of scanning,the equation of inverse kinematic analysis is carried out.The simulation of the workspace of the 3-PRRRR parallel manipulator is carried out by using MATLAB,a certain theoretical basis for the future study is provided.